Standardization of antimicrobial testing of dental devices. Issue 3 (March 2020) - Camilleri, J.; Arias Moliz, T.; Bettencourt, A.; Costa, J.; Martins, F.; Rabadijeva, D.; Rodriguez, D.; Visai, L.; Combes, C.; Farrugia, C.; Koidis, P.; Neves, C.
Abstract: Objective: Dental device is a very broad term that can be used to include any foreign material or product that is introduced in the host oral cavity to replace missing tissues. These devices are subjected to different environments which include dental hard tissues, tissue fluids, blood and saliva. All dental devices are continuously challenged microbiologically and a number of failures in clinical management are related to microbial colonization. Thus, the assessment of the antimicrobial properties of dental devices are extremely important. In this paper, a classification of dental devices is being proposed. This classification distinguishes the devices based on whether they are implantable or not, and also sub-classified based on their specific application and the substrate receiving the device. Methods and Results: A literature search was conducted to identify how dental devices have been tested with relation to the microbial strains used and whether the testing has been performed in isolation or reported with other relevant tests such as material characterization and biological activity. The results of the literature review were analyzed and recommendations for antimicrobial testing of dental devices are proposed. These recommendations include the need for the setting up of pre-testing parameters such as ageing and the details of the pre-testing sterilization procedures, as these may affect the material chemistry and the specification for antimicrobial testing to be done with specific single strains or polymicrobial that are native to the region where the device is located are also suggested. Testing can be undertaken in vitro, ex vivo and in vivo . Since the antimicrobial and biological activities influence/condition one another and the material chemistry may affect both the antimicrobial and biological testing this document also makes recommendations regarding biological assessment which can be carried out in isolation or integrated with the microbiological testing and also material testing methods including chemical and physical characterization of bulk, surface, eluted and degraded materials as well as physical characterization methods. Significance: The level of standardization of antimicrobial testing for the dental devices needs to be based on the device location and host interaction in order to increase the clinical applicability of the mentioned tests.